Partial molar pregnancy with live fetus diagnosed on second trimester: a case report - Santos, Angela (2016)
Hydatidiform mole is part of a group of diseases classified as gestational trophoblastic disease, which results from an aberrant fertilization. They are associated with an increase risk for the development of neoplasm, specifically choriocarcinoma, a malignant tumor that has a potential to locally invade the uterus and metastasize. Traditionally, moles have been categorized into complete or partial hydatidiform moles. Partial moles are most commonly triploid and are associated with the presence of a malformed fetus. Often partial moles are misdiagnosed as an incomplete or missed abortion of the first trimester. A case of a partial molar pregnancy with live fetus diagnosed on second trimester is reported. Hyperemesis gravidarum and hyperthyroidism were the clinical presentations. Human chorionic gonadotropin level was 1 891 264 mIU/mL. Fetal karyotype was 69, XXX. Surgical uterine evacuation was performed and the patient is in follow up. Partial molar pregnancy with a live fetus is a rare condition that presents a challenging diagnosis, particularly when it is detected during the second trimester of pregnancy